THE PREVALENCE OF NON-ALCOHOLIC FATTY LIVER DISEASE IN OUTPATIENTS IN THE FAR EAST FEDERAL DISTRICT - V. A. Nevzorova; M. V. Mokshina; T. A. Brodskaya; D. A. Vasil’chenkov; D. V. Blinov; T. I. Ushakova (Фармакоэкономика)
The rapidly growing incidence of obesity and diabetes mellitus, especially in developed countries, stimulates medical experts to closely study the epidemiology of non-alcoholic fatty liver disease (NAFLD). According to the published results of the epidemiological study DIREG 2, the prevalence of NAFLD in outpatients inRussiaincreased over the period from 2007 to 2015 and amounted to 37.3%. In the present report, the population of patients with NAFLD in the Far East Federal District (FEFD) was studied as part of the multicentre epidemiological study DIREG 2.The aim. To analyze the data on FEFD obtained in the DIREG 2 study and compare those with the DIREG 2 data on the entireRussia.Materials and Methods. The prospective disease registry study: epidemiological, observational, cross-sectional, multicentre study on the prevalence of NAFLD in outpatients. The total number of participating patients in FEFD was 2500, including 900 males and 1600 females. Epidemiological data were collected within two routine patient visits to the participating research centers.Results. The major result of this study is that the prevalence of NAFLD in FEFD was significantly lower than that in the entireRussia (21.4% vs 37.3%). Although the rank distribution of the concomitant diseases in FEFD patients was comparable to that in the across-Russia population, the prevalence of metabolic syndrome, menopausal syndrome and hypertriglyceridemia was significantly higher in the FEFD population.Conclusion. Despite the lower prevalence of NAFLD there is a significantly higher prevalence of disorders associated with NAFLD in the FEFD patients as compared with the acrossRussian patients from DIREG2. A set of measures preventing these risk factors from converting into full-scale disease is needed.